Downregulation of microRNA-200c-3p reduces damage of hippocampal neurons in epileptic rats by upregulating expression of RECK and inactivating the AKT signaling pathway. (1st July 2019) - Du, Yumin; Chi, Xiaowen; An, Wen
Abstract: Objective: The aim of this study is to investigate the role of mircoRNA-200c-3p (miR-200c-3p) on hippocampal neuron injury in epileptic rats through the regulation of the AKT signaling pathway by targeting RECK. Methods: The epilepsy rat model was induced by intraperitoneal injection of lithium chloride-pilocarpine. Successful modeled rats were injected with miR-200c-3p inhibitors, inhibitors NC, siRNA-negative control (NC) and RECK-siRNA. The astrocyte activation, levels of oxidative stress indexes, contents of inflammatory factors and the AKT signaling pathway-related proteins in hippocampus tissues were evaluated. Results: High expression of miR-200c-3p and low expression of RECK were found in the hippocampus tissues of epileptic rats. Downregulation of miR-200c-3p or upregulation of RECK decreased apoptosis of hippocampal neurons, expression of GFAP, content of MDA and increased the activities of GSH-Px and SOD, decreased expression of TNF-α, IL-1β and IL-6 as well as expression of p-PI3K/t-PI3K and p-Akt/t-Akt in hippocampus tissues of epileptic rats. Conclusion: Our study provides evidence that downregulation of miR-200c-3p reduces damage of hippocampal neurons in epileptic rats by upregulating RECK and inactivating the AKT signaling pathway. Graphical abstract: Image 1 Highlights: Reduced miR-200c-3p inhibits expression of RECK and inactivate AKT signaling pathway. Reduced miR-200c-3p inhibits expression of TUNEL positive cells in epileptic rats. Reduced miR-200c-3p inhibits expression of proinflammatory factor in epileptic rats. Reduced miR-200c-3p inhibits expression of GFAP in epileptic rats. Reduced miR-200c-3p reduces damage of hippocampal neurons in epileptic rats.